(untitled) (Journal of Hama University, 2021)
The aim of the research is to identify the degree of job performance of school principals in the first cycle of basic education from the point of view of the teachers of those schools in Damascus, and to reveal the significance of the differences in the averages of the teachers ’answers according to the variables (gender, years of experience and academic qualification). To achieve the objectives of the research, a questionnaire was prepared to measure the job performance of school principals, consisting of (31) items, whose validity and reliability were ascertained, and then distributed to an accessible random sample consisting of (175) teachers in the first cycle of basic education schools in Damascus. The most important results that were reached were the following: • The level of job performance of basic education school principals in Damascus was mediated from the teachers ’viewpoint on most of the items in the questionnaire. 2- There are no statistically significant differences at the level of (0.05) between the averages of teachers ’answers to the questionnaire according to the years of experience variable. 3- There are no statistically significant differences at the level of (0.05) between the averages of teachers ’answers to the questionnaire according to the scientific qualification variable. The researcher suggested conducting a study on the causes of low teachers ’expectations about the performance of principals, and training school principals on effective and modern management methods.